2023
DOI: 10.1002/cpz1.676
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Identification and Enumeration of Monocyte Subsets in Bovine and Water Buffalo Peripheral Blood

Abstract: Monocytes are innate immune system key players with pivotal roles during infection and inflammation. They migrate into tissues and differentiate into myeloid effect cells (macrophages, dendritic cells) which orchestrate inflammatory processes and are interfaces between the innate and adaptive immune responses. Their clinical relevance to health and disease of cattle (Bos taurus) and water buffalo (Bubalus bubalis), two of the most important livestock species, has been highlighted in physiologic (pregnancy) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, a role of the differential expression of other phagocytosis receptors (43) such as scavenger receptors, C-type lectin receptors, and toll-like receptors in buffalo and bovine phagocytes could be the focus of further studies. In addition, given that classical monocytes (cM) are the main phagocyting monocyte subset in both bovine and buffalo, the enhanced phagocytosis activity of bubaline monocytes could be linked to the specific phenotype of bubaline cM being positive for the activation marker CD16 + (CD14 ++ CD16 + ), which is in contrast to the CD16-phenotype (CD14 ++ CD16 − ) of bovine cM (24). Several previous in and in vivo studies have reported reduced phagocytosis in bovine neutrophils under heat stress conditions (11,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, a role of the differential expression of other phagocytosis receptors (43) such as scavenger receptors, C-type lectin receptors, and toll-like receptors in buffalo and bovine phagocytes could be the focus of further studies. In addition, given that classical monocytes (cM) are the main phagocyting monocyte subset in both bovine and buffalo, the enhanced phagocytosis activity of bubaline monocytes could be linked to the specific phenotype of bubaline cM being positive for the activation marker CD16 + (CD14 ++ CD16 + ), which is in contrast to the CD16-phenotype (CD14 ++ CD16 − ) of bovine cM (24). Several previous in and in vivo studies have reported reduced phagocytosis in bovine neutrophils under heat stress conditions (11,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In water buffalo, blood monocytes were recently classified into three different cell subsets based on the cell surface abundance of the CD14 LPS receptor and the CD16 FC receptor: CD14 +/++ CD16 −/+ classical monocytes (cMs), CD14 +/low CD16 +/++ intermediate monocytes (intMs), and CD14 -/low CD16 ++ non-classical (ncM) monocytes [ 18 ]. Although the dominant fraction of cMs (74–86% of total monocytes) with a minor population of intMs (5–8% of total monocytes) are in line with their distribution in bovine [ 33 ] and human blood [ 34 ], the frequency of bubaline ncMs (8–18% of total monocytes) seems to be higher than their bovine and human counterparts [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cM, intM, and ncM subsets were detected using multicolor flow-cytometric panels: Pacific Blue anti-CD172 a (clone CC149; Biorad Laboratories, Hercules, CA, USA), BV510 anti-CD18 (clone 6.7; BD Pharmingen, Franklin Lakes, NJ, USA); FITC anti-CD16 (clone KD1; Bio-Rad Laboratories, CA, USA); and AF647 anti-CD14 (clone MM61 A, Washington State University, Pullman, WA, USA). Clones CC149 and MM61 a were conjugated in house as reported by Grandoni et al, 2023 [ 18 ]. All labeled samples were immediately acquired using a CytoFLEX flow cytometer, and the data were analyzed using the CytExpert software (Beckman Coulter, Brea, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation